Working with Smallholders : A Handbook for Firms Building Sustainable Supply Chains - International Finance Corporation (Washington, DC, 2017)
Agribusinesses operate in a rapidly changing world. Demand for agricultural crops is expected to double as the world’s population reaches 9.1 billion by 2050. Food production will need to provide sufficient carbohydrates, proteins, and fats for the estimated 870 million people who currently lack food security. Increasing the quantity and quality of food in response to this growing demand will be a challenge for a variety of reasons. In the face of these challenges, firms recognize that the world’s 525 million smallholder farmers represent an opportunity to expand market share and secure a sustainable supply of key agricultural commodities. Smallholders also represent a potential customer base for firms marketing inputs, information, and financial services. This handbook responds to the challenges agribusinesses face by laying out the business case for working with smallholder farmers. It also provides a framework for decision making and recommends tools and resources for firms engaging with smallholder farmers. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.